2013
DOI: 10.1097/inf.0b013e318275612e
|View full text |Cite
|
Sign up to set email alerts
|

The Epidemiology of Neonatal and Pediatric Candidemia in England and Wales, 2000–2009

Abstract: Pediatric candidemia rates are beginning to fall in England and Wales. C. albicans continues to account for most Candida bloodstream infections in all age groups with no evidence of increases in non-albicans species.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
40
2
5

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(52 citation statements)
references
References 30 publications
5
40
2
5
Order By: Relevance
“…4,5,7 A 4.9% candidemia incidence was documented in the neonatal intensive care unit. This was higher than in the study conducted by Celebi S et al and Jinjian Fu et al where the incidence documented was 1.1%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…4,5,7 A 4.9% candidemia incidence was documented in the neonatal intensive care unit. This was higher than in the study conducted by Celebi S et al and Jinjian Fu et al where the incidence documented was 1.1%.…”
Section: Discussionmentioning
confidence: 99%
“…Candida species was reported in 89.6% (1320/1473) cases of fungal sepsis, with Candida albicans and Candida parapsilosis accounting for most infections in all age groups. 7 Lee JH et al: has studied on Risk factors for invasive candidiasis in infants >1500 g birth weight in the Department of Pediatrics, Duke University Medical Center, Durham, NC, USA. They concluded that Invasive candidiasis is uncommon in infants >1500 g birth weight.…”
Section: Introductionmentioning
confidence: 99%
“…Although Candida albicans has long been the most common cause of candidemia infections obtained from neonatal intensive care units (NICUs) [3, 4]. Non-C.albicans species such as Candida glabrata (C.glabrata) , Candida tropicalis (C.tropicalis) , Candida parapsilosis ( C.parapsilosis ) and Candida krusei ( C.krusei ) have emerged as the second or even the predominant pathogens that caused neonatal candidemia in some local hospitals [5].…”
Section: Introductionmentioning
confidence: 99%
“…Candidemia has emerged as an important infection control issue [3,4], because it contributes significantly to morbidity, an increased hospital stay and medical costs [5][6][7]. In children, bloodstream infections (BSIs) caused by Candida mainly occur in pediatric and neonatal intensive care units (ICUs) or patients with underlying hematological/oncologic malignancy, with Candida albicans being the most common cause of Candida infections [8][9][10].…”
mentioning
confidence: 99%